Cloning and expression of Bacillus subtilis genes in Streptomyces sp. - Salman, E. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A  local  isolate  Bacillus  subtilis     was used,  which  producingthennophilic  complex  enzyme having similar  activity  of  endogluganaseenzyme ( Endo-l,4-B-Dglucanase ).Partially digested  chromosomal  DNA of  Bacillus subtilis by EcoRl  restriction  enzyme  randomly cloned  into  Eco Rl  pSU10l   shuttle vector. The  resulted  hybrid  plasmid was  transformed  into  protoplast ofStreptomyces sp.      SH-H.The  result   revealed  that  cellulose  genes,  which  expressed   into transfonned  cells are located on chromosomal DNA fragment having size4.5Â·5 kb in size.